Comparison of solo and conventional ring yarns: effects on the compression characteristics of cut-pile carpets. Issue 4 (3rd April 2023) - Babaeipour, Akbar; Ghane, Mohammad; Hasani, Hossein
Abstract: Carpet manufacturers are continuously looking for new approach to improve the characteristics of their produced carpets in terms of appearance and durability. Material and structural parameters have a significant effect on the carpet compression properties. This study deals with characterization of the cut-pile carpets produced with Solospun pile yarns in comparison to Ring spun yarns. To this end, the acrylic pile yarns were produced in same linear density using a semi-worsted Solo- and Ring spinning systems. Both prepared pile yarns were used to produce machine-woven carpets in two different weft densities (1500 and 2000 yarns/m). Compression characteristics of the manufactured carpet samples under compression loading were evaluated. The findings revealed that the hairiness of Solospun yarn decreased by 24% and 41% for 3 and 6 mm hairs, respectively; while the yarn abrasion resistance increased by 39%. The results also revealed that the thickness loss (TL) under long-term static loading was vividly lower for the carpets produced from Solospun yarns, in comparison to Ring spun yarns. The compression characteristics such as compressibility, permanent deformation, compression energy and residual energy of the carpet samples made of the Solospun yarns were less than those made of conventional Ring spun yarns. Finally, using the Solospun yarns as carpet pile leads to higher useful life and pile recovery of the cut-pile carpets. Accordingly, these yarns are recommended to be applied in the carpet industry, instead of the Ring spun pile yarns.